Clinical Effectiveness of Programmed Cell Death Protein-1 (PD-1) Inhibitors in Advanced Cutaneous Squamous Cell Carcinoma: A Systematic Review - Wita Zahara; Subagio Subagio; Naomi Winny Tioline; Iman Agus Lisanto (Rifa'Institute, 2026)
Introduction: Advanced cutaneous squamous cell carcinoma (cSCC) is associated with a poor prognosis, particularly in patients with unresectable locally advanced or metastatic disease, while conventional systemic therapies generally achieve objective response rates below 30%. Objective: This study aimed to systematically evaluate the clinical efficacy and safety of Programmed Cell Death Protein-1 (PD-1) inhibitors in patients with advanced cSCC. Method: A PRISMA 2020-based systematic review searched PubMed, ScienceDirect, and Wiley Online Library for studies published from January 2020 to March 2026. Twenty eligible studies involving cemiplimab, pembrolizumab, or nivolumab were included. Result and Discussion: Clinical trials reported objective response rates of 44.0–45.2% for cemiplimab, 35.2–50.0% for pembrolizumab, and 61.3% for nivolumab, while real-world studies reported 35.1–80.6%. Comparative studies showed improved overall survival and durable responses. Common adverse events included fatigue, rash, and immune-related toxicities. Conclusion: PD-1 inhibitors provide effective and well-tolerated first-line systemic therapy for advanced cSCC